If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -77 = 7(1 + 4b) -77 = (1 * 7 + 4b * 7) -77 = (7 + 28b) Solving -77 = 7 + 28b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-28b' to each side of the equation. -77 + -28b = 7 + 28b + -28b Combine like terms: 28b + -28b = 0 -77 + -28b = 7 + 0 -77 + -28b = 7 Add '77' to each side of the equation. -77 + 77 + -28b = 7 + 77 Combine like terms: -77 + 77 = 0 0 + -28b = 7 + 77 -28b = 7 + 77 Combine like terms: 7 + 77 = 84 -28b = 84 Divide each side by '-28'. b = -3 Simplifying b = -3
| 4+3z-2=9z+9-7z | | 12+4(z-3)=3x+1 | | 5(r+3)-6=3(r-2) | | 3n+9=-3(2n+3) | | -28=7(7n-4) | | X^2=5*x^2-36 | | X+12+5x-17=2x+11 | | 7e^7t=11e^6t | | 5a+7b=17 | | 2(y+4)=21 | | 5*x^2-36-x^2=0 | | 3x-1=4x+9 | | x(x+3)-3=3x+1 | | 14-x=37 | | 7y-3=17 | | x^2+kx+8=k | | 5(m+4)-7= | | 5*x^2-x^2=36 | | 2(x^2-192)=0 | | .66d+1=16-d | | 2(x-3)+5=4x+7 | | -(a-4)=6 | | 10(a+1)-14a=9+(4a-1) | | 0=2x^3-6x^2+8x-3 | | -2(4x-9)=-8x+18 | | 7+5y=39+y | | 119+40+4x=180 | | 400-40w=80 | | 125.00+5.75=228.50 | | 9xh=-63 | | 6x-43=65+x | | 4x-15=1x-13 |